P259 Cost analysis of implementing a pe pathway incorporating 3-level wells scoring, perc rules and age-adjusted d-dimers. (15th November 2016) - Mahmood, A; Durrans, C; Naik, S; Anwar, M
Abstract : Background: Acute pulmonary embolism (PE) is a common presentation. Currently NICE recommends 2-level Well scoring, which may over-investigate patients leading to unnecessary anti-coagulation and contrast-related risks and significant financial costs. We investigated whether further risk stratification using a combination of 3-level Wells scoring, PERC rules and age-adjusted D-dimers could minimise costs and enhance patient safety. Methods: Retrospective analysis of patients who underwent CTPA and had complete data between September 2014 and August 2015 was carried out. Wells scores, PERC scores and age-adjusted D-dimers were calculated and compared against CTPA findings. Results: Out of 1174 patients who underwent CTPA, 1158 had complete data set. Application of PERC rules to low-risk patients (Wells score 0–1; n = 311, 27%) would have avoided 64 CTPAs, but missed 3 PEs, with a 95% sensitivity (95% CI: 0.85–0.97), 24% specificity (95% CI: 0.19–0.30), and avoided 56 D-dimers. For intermediate-risk patients (Wells score 2−7), age-adjusted D-dimers would have avoided 265 CTPAs but missed 32 PEs, with an 81% sensitivity (95% CI: 0.74–0.86), 50% specificity (95% CI: 0.45–0.55). High-risk patients should proceed directly to CTPA. The combination of 3-level Wells scoring, PERC rules, and age-adjusted D-dimers would have avoided 450 CTPAs (39%) but missed 39 PEs (8%), with an estimated financial saving of at least £255, 150 (local CTPA tariff £567). Non-age adjusted D-dimers would have reduced this avoiding 132 CTPAs (11%), and missing only 7 PEs (5%). Further saving would have resulted from avoiding D-dimer testing in low risk PERC negative patients, and high risk patients. Conclusion: The use of a PE algorithm incorporating multiple clinical assessment tools results in a pathway which can help rationalise the number of CTPAs performed and D-dimers requested, without significantly increasing the proportion of missed PEs. References: Forciea MA, et al . Evaluation of patients with suspected acute pulmonary embolism: best practice advice from the clinical guidelines committee of the American College of Physicians. Ann Intern Med 2015;163 (9):701–11. Singh B, et al . Pulmonary embolism rule-out criteria (PERC) in pulmonary embolism–revisited: a systematic review and meta-analysis. Emerg Med J 2013;30 (9):701–6.